COMPREHENSIVE REVIEW OF TRAINING PROGRAMS FOR ANESTHESIA TECHNICIANS: EVALUATING CURRICULUM EFFECTIVENESS AND CLINICAL COMPETENCY - Abed Salem Manea Aljawad, Khalid Abdullah M bani Humayyim, Rami Mohammed S Alshaiban , Ali Waleed ali mahabbat , Abdullah Hassan Al Thaiban, Turki Mana Ali Al shahi , Saeed Hamad Saleh Al Abataheen, Abdul Rahman Askar M Lasloum; Jaber Misfer AAlsloom, Abdullah Jaber Mahdi Al Yami, Hamad Mohammed H AL amer, Mesfer Ahmed M AL baalatahin, Saad Mohammed Alaba Altahin, Saeed Ahmed M AL baaltahin (Chelonian Research Foundation, 2023)
This comprehensive review critically evaluates the training programs developed for anesthesia technicians to test their efficacy, how the curriculum contributes to the acquisition of clinical competence, and the resultant effect. The review aims to assess the weaknesses, strengths, and areas for enhancement within the anesthesia technician education program through a systematic literature assessment. By determining the auditing of curriculum materials, educational approaches, and outcomes, this review aims to present something that, at the moment, is an examination of the current landscape of anesthesia technician training. Recognizing where the knowledge falls short and highlighting the areas for improvement is precisely what this review will be coming after. This review is another one of those efforts that aim to optimize anesthesia technicians' education. On the whole, the results of the study will become a source of guidance for educators, practitioners, and policymakers to develop educational programs to foster improved quality of anesthesia technician education and to help provide better outcomes for patients who are to undergo surgical procedures. Keywords: Anesthesia Technicians, Training Programs, Curriculum, Clinical Competency.